2018
DOI: 10.1021/acsami.7b15263
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Mixed Cation Metal Halide Perovskites in Air

Abstract: We study the thermal stability in air of the mixed cation organic-inorganic lead halide perovskites CsFAPb(IBr) and Cs(MAFA)Pb(IBr). For the latter compound, containing both MA and FA ions, thermal decomposition of the perovskite phase was observed to occur in two stages. The first stage of decomposition occurs at a faster rate compared to the second stage and is only observed at relatively low temperatures (T < 150 °C). For the second stage, we find that both decomposition rate and the activation energy have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 36 publications
2
104
0
Order By: Relevance
“…Recently, the synergetic effect of organic and halide ions on thermal stability has also been investigated, showing that the synchronized release of FA + and Br − was the determinant factor for thermal stability . Tan et al investigated the thermal stability of two mixed systems Cs 0.17 FA 0.83 Pb(I 0.83 Br 0.17 ) 3 and Cs 0.05 (MA 0.17 FA 0.83 ) 0.95 Pb(I 0.83 Br 0.17 ) 3 in air by XRD measurements, revealing that a fast rate decomposition of the triple‐cation perovskites was mainly involved MA + but the slow stage was related to FA + . Therefore, combined with the compositional engineering to tune the tolerance factor as discussed above, it is possible to optimize the annealing temperature and time for tuning the film quality and electronic structures of perovskites as well as high‐performance PeSCs.…”
Section: Degradation Induced By Extrinsic Factorsmentioning
confidence: 99%
“…Recently, the synergetic effect of organic and halide ions on thermal stability has also been investigated, showing that the synchronized release of FA + and Br − was the determinant factor for thermal stability . Tan et al investigated the thermal stability of two mixed systems Cs 0.17 FA 0.83 Pb(I 0.83 Br 0.17 ) 3 and Cs 0.05 (MA 0.17 FA 0.83 ) 0.95 Pb(I 0.83 Br 0.17 ) 3 in air by XRD measurements, revealing that a fast rate decomposition of the triple‐cation perovskites was mainly involved MA + but the slow stage was related to FA + . Therefore, combined with the compositional engineering to tune the tolerance factor as discussed above, it is possible to optimize the annealing temperature and time for tuning the film quality and electronic structures of perovskites as well as high‐performance PeSCs.…”
Section: Degradation Induced By Extrinsic Factorsmentioning
confidence: 99%
“…Secondly, the selection of cell components must be reconsidered thinking at a large‐scale commercialization because some of the standard materials (like HTMs) currently used in lab‐scale devices have unrealistic costs for a third generation photovoltaic technology . The versatility of perovskites has been further enriched in the last years because it has been shown that they present tuneable properties in function of several experimental factors, such as morphology, choice of cations, metals and halide elements, mutual composition and preparation procedure . In this scenario, it emerged that perovskites with mixed cations and halides are thermally and structurally more stable than the pure perovskite compounds: this observation opened a wide experimental and theoretical research activity, aiming at maximizing PSCs performance by choosing suitable elements, ions and functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…[63] The versatility of perovskites has been further enriched in the last years because it has been shown that they present tuneable properties in function of severale xperimental factors, such as morphology,c hoice of cations, metals and halide elements, mutual composition and preparation procedure. [64,65] In this scenario, it emerged that perovskites with mixed cations and halidesa re thermally and structurally more stable than the pure perovskite compounds:t his observation openedawide experimental and theoretical research activity,a iming at maximizing PSCs performance by choosing suitable elements, ions and functional groups. The resulting stability will be precious also for the commercial integration of PSCs with energy storage facilities.…”
Section: Introductionmentioning
confidence: 99%
“…The multi‐cations in the perovskite are energetically favorable compared with a single‐cation perovskite, as a result of reduced free energy due to an increase in the entropy of the system . Moreover, multi‐cation perovskites display high heat durability along with long‐term stability and high PCE values . The A site cations mainly stabilize the perovskite structure, whereas the halides dictate the optical properties of the perovskite, since their hybridization with the B cation orbitals determines the E g value of the material …”
Section: Introductionmentioning
confidence: 99%